Role of Extracellular Vesicles in Hematological Malignancies. (25th October 2015) - Raimondo, Stefania; Corrado, Chiara; Raimondi, Lavinia; De Leo, Giacomo; Alessandro, Riccardo
Abstract : In recent years the role of tumor microenvironment in the progression of hematological malignancies has been widely recognized. Recent studies have focused on how cancer cells communicate within the microenvironment. Among several factors (cytokines, growth factors, and ECM molecules), a key role has been attributed to extracellular vesicles (EV), released from different cell types. EV (microvesicles and exosomes) may affect stroma remodeling, host cell functions, and tumor angiogenesis by inducing gene expression modulation in target cells, thus promoting cancer progression and metastasis. Microvesicles and exosomes can be recovered from the blood and other body fluids of cancer patients and contain and deliver genetic and proteomic contents that reflect the cell of origin, thus constituting a source of new predictive biomarkers involved in cancer development and serving as possible targets for therapies. Moreover, due to their specific cell-tropism and bioavailability, EV can be considered natural vehicles suitable for drug delivery. Here we will discuss the recent advances in the field of EV as actors in hematological cancer progression, pointing out the role of these vesicles in the tumor-host interplay and in their use as biomarkers for hematological malignancies.